HUBUNGAN PENGETAHUAN IBU DENGAN PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) PADA BAYI DI PUSKESMAS BITUNG BARAT KOTA BITUNG - Els Ivi Kulas (Jurnal GIZIDO, 2013)
Complementary feeding ( MP - ASI ) should be given to babies over 6 months of agebecause the digestive system is relatively perfect and in accordance with the needs andthe digestibility of the baby . Health Center West in Bitung Bitung , data showed that thereare still mothers who give supplementary food for infants aged less than 6 months on thegrounds of lack of milk production and the baby crying , so they provide extra food to meetthe needs of the baby . The general objective of this study is to determine the relationshipbetween maternal knowledge by providing complementary feeding . The specific objectiveis to describe the characteristics of the mother , knowing the knowledge of giving MP - ASI, knowing provision of complementary feeding and determine the relationship betweenknowledge by providing complementary feeding . This type of research is a cross sectionalanalytic approach . Population is all the mothers who have infants aged 0-12 months in theWest Bitung Bitung City Health Center 300 people . Sampling as much as 20 % of the totalpopulation and the number of samples obtained by 60 respondents based on purposivesampling . Independent variables and the dependent variable is knowledge is giving MP –ASI. Data analysis using univariate and bivariate frequency distributions using Chi - squaretest . The results showed the majority of respondents aged between 20-35 years (71.7 %),education completed high school / equivalent ( 48.3 % ) , work as housewives ( 75.0 % )knowledge of the provision of MP - ASI partially large ( 56.7 % ) were good , most of therespondents ( 63.3 % ) did not provide complementary feeding in infants and there is asignificant relationship between knowledge of the provision of complementary feeding ( p <0,05 )